Balaghah Analysis of Uslub At Thibaq and the Various Kinds, Types and Meanings in Surah An Najm/ Tahlîlu Balâghiyin ‘an Ushlûb at-Thibâqi wa ‘anwâihâ wa Sawrihâ wa Ma’ânîhâ fi Sûrah an-Najm - Hendri, Muspika; Efendi, Aprijon; Muhammad, Adamu Abubakar (Al-Manar, 2023)
Al-Qur'an has a beautiful language style that was truly extraordinary and incomparable, both beauty in terms of pronunciation and its meaning.  To explore and understand the beauty of the Al-Qur'an language was required the Arabic language sciences mastery, especially the Balaghah.  Among the discussion of the Balaghah was Uslub At Thibaq.  Uslub At Thibaq was the part of Badi’ science, where Badi’ science was a branch of Balaghah science.  Uslub At Thibaq discussed about the beauty of the Arabic language meaning that was used in Al-Qur'an.  This research aimed at knowing what verses contained Uslub At Thibaq in surah An-Najm both in terms of Uslub At Thibaq, the type, and the meaning contained therein, and how the learning relevant methods were used by teachers when teaching Uslub At Thibaq material to their students, so the students could easily in understanding and mastering the material received from their teachers.  It was a library research.  This research used primary and secondary sources related to the object of this research.  The method used in collecting data was the Bahsun Maktabiyun method with the observation, reading and studying books methods related to the research.  Content analysis using tables was used for analyzing the data.  The findings of this research showed that there were 8 verses containing Uslub At Thibaq from the 62 verses in surah An Najm, in terms of its types, there were 8 Thibaq Ijab and 1 Thibaq Salab, then in terms of kind, there were 4 Thibaq derived from the word Isim, and 5 Thibaq derived from the word Fi'il and each sentences containing Uslub At Thibaq that have the meaning contained in them